CHARACTER EXAMINATION IN ANTON CHEKHOV'S FAT AND THIN - Agnes Tianingsih; Dinda Salsabila; Roida Febrianti (Cahaya Ilmu Bangsa Institute, 2024)
This study aims to explore the impact of societal hierarchies on personal relationships and behavior through the characters in Anton Chekhov's